Nightless city: Impacts of policymakers' questions on overtime work of government officials - Natsuki Arai; Masashige Hamano; Munechika Katayama; Yuki Murakami; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2023)
We quantify the impact of unexpectedly assigned tasks on overtime work in the context of Japanese government officials. Data on overtime work are typically less reliable. We overcome this problem by using mobile phone location data, which enables us to precisely measure the nighttime population in the government-office district in Tokyo at an hourly frequency. Exploiting the exogenous nature of task arrivals, we estimate impacts on overtime work. We find that, in response to a newly assigned task, overtime work initially decreases and then increases persistently. Institutional changes to relax the time constraint and improve the working environment of government officials play a part in mitigating overtime work, but persistent increases in overtime work remain. We provide a simple model of optimal work al- location and show that distortion in intertemporal task allocation can account for the observed responses.
Keywords: C22; H11; J22; 330; mobile location data; overtime work; local projection; government officials